PENGARUH MODEL PEMBELAJARAN SOCIO-BIOLOGICAL CASE BASED LEARNING TERHADAP KETERAMPILAN BERPIKIR KRITIS MAHASISWA BIOLOGI FMIPA UNIVERSITAS NEGERI MALANG - Pratiwi, Herwim Enggar; Suwono, Hadi; Susilo, Herawati (Jurnal Pendidikan Biologi, 2015)
The purpose of this research is to determine the effect of Socio-Biological Case Based Learning model toward critical thinking skills. This study is an quasy experimental design by nonrandomized pretest-posttest control group design conducted in the department of Biology in State University of Malang in 2015. The data was collected from pretest and posttest. The result showed that there was significant influence of critical thinking skills on general Biology among Socio-Biological Case Based Learning and conventional model. The average difference in conventional model for pretest and posttest is 18,21 while in Socio-Biological Case Based Learning is 36,92. Based on gain score, the increase in conventional model is 62,80% while Socio-Biological Case Based Learning model is 74,03%.